واقع الإتصال الشخصي بين الطبيب والمريض في ظل جائحة كورونا - بارود ريهام; د. علي بن عزوزي (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدارسة هددددال الدارسدددة الوالعدددة اا دددخ ا بيددداط ال خيدددي دددظل الئحظدددر االددددر ادددي ددد ا ودددة را دددا ا ددد الدؤسسة العد معة ا ست فا عة احدظدة دل جيظمدة ل دة ااطد او د ا دا الدل مواالدة التعدرف جمدل عد كدداو اا ددخ ا بيدداط ال خيددي ددظل الئحظددر االدددر اددي دد ا وددة را ددا مددل ددلط الئددرا التسددا ط الر عسدددي لالددداالعة افبدددي عددد ددداو اا دددخ ا بيددداط ال خيدددي دددظل الئحظدددر االددددر ادددي ددد ا ودددة ك را ا؟ا ندرج ضدل هذا التسا ط بسا ت ارععة - ما طحععة اا خ ا بياط ال خيي ظل الئحظر االدر اي ا وة را ا ؟ 1 - ماه ال ا ا بياط الذي هر ظل الئحظر االدر اي ا وة را ا؟ 2 - ماهي اسا ا بياط الحديمة التي استخدمها الئحظر االدر اي ا وة را ا؟ 3 كدا اجتدددت الااحةدة ادي ارسدتها جمدل الددنهف ال ددفي ام اات ددخ الحعا دات منهدا ا سدتحعاو االدلح دة لتوقظددا اهددداف هددذا الدارسددة بدد ا تعددار طاقددة ج دد ا عة مددل دل د و مد دة بتيد اسد دي لمدر دخ اليمد مفددر ة33 الديتدد اسدددات السدددا قةش ا يدددا ص جظندددة ا ضدددعل النتدددا ف لمتفسدددظرش االدنا دددة ادددي ضددد د اسطدددار الن دددري االدر الاوثش مينا إلل ميد جة مل النتا ف : - مثرت ا وة را ا سماا جمل جدمعة ا بياط ال خيي ظل الئحظر االدر . - ساه الويدر اليدوي ا التااجدد اليسددي -التدي بد التيكظدد جمظهدا -ادي ا تهداد عد العدا ات اا ت دار جا ات ديدة. - مثدددرت إ ددداردات التددددا ظر ا حتارة دددة ليا ودددة را دددا مدددل حيدددر اجدددزط ابااجدددد إ تدددداجي جمدددل اليدددوة النفسعة ااار ا مقل ة م و و القما االت بر اا كتئاب االخ ف مل الدستقح اسضاا لمدم االعزلة. - سددداهدل التين ل عدددا ادددي بخ عددد افثدددار السدددمحعة لمعدددزط ا تدددداجي ددددا حمدددل اسدددا الت ادددد موددد ا بيددداط ال خيدددي ا ددد ل ددد ادددي مختمدددل الدناسددداات ااسدددر ة اا تداععدددة عدددد او اددددا ا بيددداط ال خيي الوض ري مامفا امفت حا جمل التعرض لمخئر د بي و تعيتها الد ت. اددي برظددارت ععددة اددي السددم عات ا ت ت 11 - سدداهدل ا وددة اظددد دا م االيداجد دخ ا الديتدد در دة ااد داععد ش عضا مل هذا الترظارت . ابخذ طا عا سمحعا ظندا ابخذت م رى طا عا إ يا عا Anstract: The current study aimed to try to identify the reality of personal communication between the doctor and the patient in light of the Corona pandemic within the public hospital institution, Hamida Ben Ajila, in the state of Laghouat, by asking the main question of the following problem: How was the reality of communication between the doctor and the patient in light of the Corona pandemic? The personal relationship between the doctor and the patient in light of the Corona pandemic? This question includes sub-questions 1- What is the nature of the reality of personal communication between the doctor and the patient in light of the Corona pandemic? 2- What is the form of communication that has emerged between the doctor and the patient in light of the Corona pandemic? 3- What are the alternative means of communication used by the doctor and patient in light of the Corona pandemic? In her study, the researcher also relied on the descriptive approach and data collection tools, including questionnaire and observation, to achieve the objectives of this study. A random layer was selected from the total population for the study, consisting of 53 individuals. The results were subjected to interpretation and discussion in light of the theoretical framework, previous studies, and the characteristics of the research sample. We concluded with a set of Results : The Corona pandemic negatively affected the process of personal communication between the doctor and the patient. Quarantine and physical distancing - which were emphasized - contributed to the end of some customs and the spread of new ones. The precautionary measures for the Corona pandemic, such as quarantine, isolation, and social distancing, have affected the mental health of individuals and created an atmosphere charged with anxiety, tension, depression, and fear of the future, in addition to boredom and isolation. Technology has contributed to alleviating the negative effects of social isolation, and social media has replaced face-to-face personal contact on various family and social occasions after in-person personal contact has become costly and opens up exposure to danger that may result in death. The Covid-19 pandemic has contributed to qualitative changes in the social behaviors of community members and groups. Some of these changes have taken a negative character while others have taken a positive character